Overview of energy storage technologies and a short-term storage application for wind turbines - Christodoulides, Paul; Marouchos, Christos; Kalogirou, Soteris A.; Florides, Georgios A.; Lazari, Lazaros; Argyrou, Maria C. (My University, 2016)
The spreading of renewables has become stronger due to the increased air pollution. On the other hand, the penetration of renewable energy technologies causes major problems to the stability of the grid. Along with the fluctuations of the renewable energy technologies production, storage is important for power and voltage smoothing. Thus, storage technologies have gained an increased attention considering the distributed generation. This paper presents an up to date comprehensive overview of energy storage technologies. It incorporates characteristics and functionalities of each storage technology, as well as their advantages and drawbacks compared with other storage technologies. A demonstration of a short-term energy storage application in a gridconnected small wind turbine is given. The circuit is operated at the maximum power point (MPP), succeeding its connection and synchronization with the low-voltage grid. It also utilizes the energy generated by the wind turbine when a fault appears for a short period of time, through the supercapacitor.
Keywords: Energy storage; Grid; Renewable energy sources; Supercapacitors; Wind turbine